Germanium photodetectors on Silicon-on-insulator grown with differential molecular beam epitaxy in silicon wells - Kaschel, M.; Schmid, M.; Oehme, Michael; Werner, J.; Schulze, J. (Solid-State Electronics, 2011)
In this paper we propose a method for growing fast Germanium pin photodetectors in pre-patterned areas on a Silicon-on-insulator substrate. The layers are deposited by means of molecular beam epitaxy and structured by chemical mechanical polishing. A comparison of the electrical and optical characteristics between a photodetector grown with the proposed method and a reference detector grown on a planar Silicon substrate is made indicating only minor differences. © 2011 Elsevier Ltd. All rights reserved.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Differential molecular beam epitaxy; Germanium; Optical responsivity; Photodetector; Pin; SOI